1998
DOI: 10.1093/ajcp/109.6.733
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Angiogenesis in Stage II Colorectal Carcinoma:Association With Survival

Abstract: We studied the frequency of microvessels in T3 NO MO colorectal carcinomas from patients with widely different survival times. Microvessels (<50 nm diameter) were enhanced by immunostaining with antibody to factor VHI-related antigen and counted in 40x high-power fields in sections of resected carcinomas from 9 patients who died of disease in 24 months or less (short-term survivors) and 13 who had no evidence of disease at 109 months or longer (longterm survivors). The means of the 10 highest counts for each c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 9 publications
3
19
0
2
Order By: Relevance
“…It is difficult to compare our findings with those reported in other studies due to the heterogeneity of case series with respect to stage and treatment. While some studies (Bossi et al, 1995;Frank et al, 1995;Mooteri et al, 1996;Takebayashi et al, 1996;Amaya et al, 1997;Takahashi et al, 1997;Banner et al, 1998;Giatromanolaki et al, 1999;Vermeulen et al, 1999) found a direct or no relation between high angiogenic activity and poorer prognosis, we observed a trend of a better prognosis for patients with high MVD tumours, in agreement with recently published results obtained on large case series (Lindmark et al, 1996;Abdalla et al, 1999). Similar results have already been reported in breast cancer (Protopapa et al, 1993;Axelsson et al, 1995;Medri et al, 2000).…”
Section: Molecular and Cellular Pathologysupporting
confidence: 93%
“…It is difficult to compare our findings with those reported in other studies due to the heterogeneity of case series with respect to stage and treatment. While some studies (Bossi et al, 1995;Frank et al, 1995;Mooteri et al, 1996;Takebayashi et al, 1996;Amaya et al, 1997;Takahashi et al, 1997;Banner et al, 1998;Giatromanolaki et al, 1999;Vermeulen et al, 1999) found a direct or no relation between high angiogenic activity and poorer prognosis, we observed a trend of a better prognosis for patients with high MVD tumours, in agreement with recently published results obtained on large case series (Lindmark et al, 1996;Abdalla et al, 1999). Similar results have already been reported in breast cancer (Protopapa et al, 1993;Axelsson et al, 1995;Medri et al, 2000).…”
Section: Molecular and Cellular Pathologysupporting
confidence: 93%
“…After exclusion of the references which were out of the scope of our meta-analysis, there remained 45 studies dealing with MVD (see Appendix B) and 27 dealing with VEGF expression (see Appendix C), representing a total of 56 independent studies. Some of these articles did not fulfil our inclusion criteria (mainly because they did not mention survival data), six for MVD (Vermeulen et al, 1995;Banner et al, 1998;Nanashima et al, 1998;Kondo et al, 2000;Barozzi et al, 2002;Saad et al, 2004) and five for VEGF (Nanashima et al, 1998;Kondo et al, 2000;Seto et al, 2000;Barozzi et al, 2002;Saad et al, 2004). One study was written in Chinese language, with an English abstract and did not seem to mention survival data (Liu et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Although most studies of advanced colorectal cancer have highlighted the prognostic value of microvessel counting, there have been some controversial data (3,17) which can be attributed to the use of methodology that vary considerably in the microvessel counting method, originally introduced by WEIDNER et al (32) and recently modified by VERMEULEN et al (30) . However, authors using this conventional microvessel counting method as BANNER et al (1) found higher MVD in colorectal carcinoma patients who had longer survival, but it was not statistically significant and PAVLOPOULOS et al (19) found prognostic significance in advanced colorectal carcinoma regarding only vascular ramifications and the total vascular area.…”
Section: Microvessel Count and Patient Survivalmentioning
confidence: 99%